2021
DOI: 10.3390/ijms22094645
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Hypertrophy and Fibrosis Are Associated with Cardiomyocyte Beta-Catenin and TRPC6/Calcineurin/NFAT Signaling in Spontaneously Hypertensive Rats with 5/6 Nephrectomy

Abstract: Background: Arterial hypertension (AH) is associated with heart and chronic kidney disease (CKD). However, the precise mechanisms of myocardial remodeling (MR) in the settings of CKD remain elusive. We hypothesized that TRPC6, calcineurin/NFAT, and Wnt/β-catenin signaling pathways are involved in the development of MR in the background of CKD and AH. Methods: Early CKD was induced by performing a 5/6 nephrectomy (5/6NE) in spontaneously hypertensive rats (SHR-NE). Sham-operated (SO) SHR (SHR-SO) and Wistar Kyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
0
12
1
Order By: Relevance
“…Although we could not prove that in the present study, our results at least show that TCF/LEF-1 pathway is not the only downstream effector, since ICG-001 did not exhibit the same efficacy as KYA1797K. Since Wnt/β-catenin signaling has been involved in the pathogenesis of a variety of tissue fibrosis [42][43][44][45][46][47], we believe that KYA1797K, which could induce the destabilization of β-catenin, may also have beneficial effects on these fibrotic disorders.…”
Section: Discussioncontrasting
confidence: 69%
“…Although we could not prove that in the present study, our results at least show that TCF/LEF-1 pathway is not the only downstream effector, since ICG-001 did not exhibit the same efficacy as KYA1797K. Since Wnt/β-catenin signaling has been involved in the pathogenesis of a variety of tissue fibrosis [42][43][44][45][46][47], we believe that KYA1797K, which could induce the destabilization of β-catenin, may also have beneficial effects on these fibrotic disorders.…”
Section: Discussioncontrasting
confidence: 69%
“…Almost all TRPC isoforms are differentially expressed in left ventricular tissue and cells isolated from experimental animal models of LV remodeling and dysfunction, and in myocardial biopsies from failing human hearts ( Table 1 and Figure 1 ). Indeed, in different in vivo experimental rodent models of hypertrophy and HF induced by pressure or volume overload (abdominal, ascending or transverse aortic constriction, Dahl salt-sensitive, spontaneously hypertensive (SHR), myocardial infraction, ischemia-reperfusion injury) or by neurohormonal stress (PE, Endothelin-1 (ET-1), AngII, Isoproterenol), an increased expression of TRPC1 [ 54 , 57 , 59 , 65 , 82 , 88 , 89 , 90 , 91 , 92 ], TRPC2 [ 90 ], TRPC3 [ 59 , 90 , 93 , 94 , 95 , 96 ], TRPC4 [ 59 , 81 , 97 ], TRPC5 [ 83 ] and TRPC6 [ 59 , 72 , 81 , 90 , 94 , 95 , 96 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ] has been reported. Additionally, increased TRPC1 and TRPC5 expression in failing human hearts [ 93 , 105 , 106 ], increased TRPC6 mRNA in human LV with dilated cardiomyopathy [ 100 ], and decreased expression of TRPC4 in isolated LV myocytes from patients with ischemic cardiomyopathy and severe HF have been shown [ 105 , 107 ] (…”
Section: The Soce In the Adverse LV Remodelingmentioning
confidence: 99%
“… 4 , 5 Recent studies have revealed that TRPC6/Calcineurin/NFAT and cWnt/β-catenin signaling pathways are associated with pathological hypertrophy. 6–8 Jia et al reported that Bcl2-associated athanogene 3 (BAG3) promotes physiological hypertrophy by activating the Akt/mTOR pathway while attenuating pathological hypertrophy by inhibiting the TRPC6/CaN/NFAT pathway. 9 Although a beneficial adaptive response initially, myocardial hypertrophy transforms into a detrimental change and progresses into HF eventually under persistent pathological stimuli.…”
Section: Mechanisms Of Ventricular Remodeling Following Myocardial In...mentioning
confidence: 99%